Legal Vacuum Regarding the Election of the Head of the District Which is Followed by Only a Single Candidate - Hono Sejati; Wieke Dewi Suryandari (Mahkamah : Jurnal Riset Ilmu Hukum, 2025)
This study seeks to examine the legal vacuum surrounding regional head elections that feature only a single candidate, as well as the legal implications that arise from this scenario. In a democratic system, the principle of popular sovereignty necessitates a fair and free electoral process; however, the absence of clear regulations for regional head elections with a solitary candidate can jeopardize the integrity of this principle. Employing a normative legal methodology with both legislative and conceptual approaches, this study investigates various regulations that govern regional head elections and assesses how this legal vacuum impacts the electoral process and the constitutional rights of citizens. Additionally, the study identifies several strategies to address the legal vacuum, which include establishing clear legal provisions for the election process involving a single candidate, implementing a plebiscite mechanism, and enhancing transparency throughout the electoral process. The findings suggest that a more definitive and explicit legal framework is essential to uphold the principle of popular sovereignty in regional head elections featuring a single candidate.